The implementation of smart measurement from the viewpoint of the consumers - Szunyog, Vivien (Studia Mundi – Economica, 2015)
“Electricity suppliers, in accordance with the appropriation of the European Union, the Hungarian government, and the Hungarian Energy and Public Utility Regulatory Authority, have begun the preparations for implementing the so-called smart measurement system.” – That is how those consumers who were planned to receive a smart meter in their household were notified. The new meter was planned to have been set up within a month by the company’s employed mechanics. These are the reasons why I have chosen to examine the installment of smart meters from the viewpoint of the consumers. What benefits would this change bring to them? How can they save money by using smart meters? How can they influence their consumption? Are they willing to change their consumption habits? In my work, the starting point will be a sociodemographic attitude research that has already been carried out. Besides all this, I am going to describe the disadvantages of smart meters as well. I am going to present what other inventions suppliers are planning after the installment of smart meters by performing some calculations with the smart web portal’s smart tariff calculator. Finally, I am going to summarize the most important thoughts and conclusions.